Analisis Faktor-Faktor yang Mempengaruhi Minat Investasi Mahasiswa di Pasar Modal: Studi kasus pada Mahasiswa Universitas Tunas Pembangunan Surakarta, Universitas Dharma AUB Surakarta, dan Universitas Slamet Riyadi - Rahma Zuhria Ningrum; Rahmatya Widyawati; Syahriar Abdullah; Supartini; Susilaningtyas Budiana Kurniawati (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to analyze the factors that influence student investment interest in the capital market. The methods used in this study are quantitative methods and sampling techniques, namely using saturated sampling techniques with a purposive sampling approach, in accordance with predetermined criteria. The sample of this study was 51 students who met the criteria. This study used primary data obtained through g-form then disseminated through whatsAap. The g-form questionnaire is arranged with a likert scale of 1-5. The variables used in this study are financial literacy variables (X1), investment knowledge (X2), motivation (X3), and investment interest (Y) in the capital market. Data analysis techniques in research are descriptive statistical analysis, data quality tests, classical assumption tests, multiple linear regression tests, and hypothesis tests. Data processing is done with the help of SPSS software version 25. Based on the results of the study, it shows that the results of the financial literacy t test obtained t count (-0.616) < t table (2.012) can be concluded if financial literacy does not affect student investment interest in the capital market, while investment knowledge obtained t count (2.954) > t table (2.012) can be concluded if investment knowledge affects student investment interest in the capital market and motivation obtained t count (2.277) > t table (2.012) can It is concluded that motivation affects students' investment interest in the capital market. Simultaneously, based on the results of the f test, it shows that together the variables of financial literacy, investment knowledge, and motivation affect students' investment interest in the capital market.